The importance of hibah in property management: a study on muslim's investors in ASNB Shah Alam / Nur Atiqah Yusoff - Yusoff, Nur Atiqah (Academy of Contemporary Islamic Studies, 2018)
Since recently, issues on frozen asset which can lead to loses in economic value are closely related with Islamic inheritance especially when heirs are not claiming their inheritance. The purpose of this paper is to assess the importance of Hibah in property management. The paper has used the data from primary data by contributed the questionnaire to 100 of Muslim's investors in Amanah Saham Nasional Berhad (ASNB) Shah Alam. Besides, the secondary data such as journal and electronic sources were used to getting more information about Hibah. Other than that, the researcher used descriptive statistics on Likert scale questions to measure the agreement of respondents on the question given. The researcher also used frequency analysis to identify the gender, age, and marital status, and education level, monthly income of respondents, health status and total assets. In order to get the result of this study, the researcher has used correlation analysis and it showed there are significant relationships between knowledge, benefit of Hibah and Hibah as an alternative with Hibah in property management. The reliability analysis also used by researcher to testing the reliable of the items measure and the result indicated all variable in this study were reliable.